HUBUNGAN KOMPETENSI DAN MOTIVASI KETUA KELOMPOK TANI TERHADAP PENDAPATAN USAHATANI TEBU PROGRAM MITRA MANDIRI GUNUNG MADU PLANTATIONS DI KABUPATEN LAMPUNG TENGAH - Ernas Nurcahyo; Sudarma Widjaya; Eka Kasymir (Lampung University, 2017)
This study aims to determine: the level of competence, and motivation of leaders of farmer groups which make partnership with Gunung Madu Plantations on Independent Program; the correlation of the competence and the motivation on farming income. This research is a case study and ues a census method. Respondents are all farmer group leaders joining independent program in Gunung Madu Plantations in Central Lampung regency. The research variables consist of a number of dimensions and indicators were measured by using Likert scale. The methods of data analysis are using quantitative descriptive and categorization as well as Rank Spearman test. The results showed that the level of competence and motivation of farmer group leaders are in the high category and sugar cane farming income is in high category; the competence and motivation of farmer group leaders have a close ties to the sugar cane farming income. Key words: competence, motivation, sugar cane farming, income